2013
DOI: 10.1177/0731684413489755
|View full text |Cite
|
Sign up to set email alerts
|

Thermally conductive polymer compounds for injection moulding: The synergetic effect of hexagonal boron-nitride and talc

Abstract: The aim of the research was to investigate and maximize the thermal conductivity of the polymer compounds with low filler content (<30 vol%). The study focused on the effect of the matrix material, the filler type, the processing method and the interaction of the fillers. It was concluded, that the compression moulded samples have higher thermal conductivity than the injection moulded ones due to the segregation effect and the orientation of the anisotropic fillers. Furthermore thermal conductivity can be impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Alig et al [34,35] showed that the processing and thereby the shear prehistory influences the (electrical) conductivity of composites. Though, with the addition of thermal conductive fillers, processing conditions as described by Ng et al [36] and Kovacs et al [37] heavily influence dispersion, orientation and degradation of the filler. Furthermore, both studies showed that the thermal conductivity also depends on the sample shaping method.…”
Section: Thermally Conductive Polypropylenementioning
confidence: 99%
“…Alig et al [34,35] showed that the processing and thereby the shear prehistory influences the (electrical) conductivity of composites. Though, with the addition of thermal conductive fillers, processing conditions as described by Ng et al [36] and Kovacs et al [37] heavily influence dispersion, orientation and degradation of the filler. Furthermore, both studies showed that the thermal conductivity also depends on the sample shaping method.…”
Section: Thermally Conductive Polypropylenementioning
confidence: 99%
“…Single-specimen hot plate apparatus was used according to the publication of Suplicz et al [33]. In this equipment, the heat flows in a single direction between the hot plate and the cold plate through the specimen, which is a simpler apparatus than a conventional two-specimen.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, an in-house developed one-specimen hot-plate apparatus was used, presented in previous work [28]. For the measurements, 80x80 mm specimens were printed with thicknesses of 2, 4 and 8 mm.…”
Section: Measurements Of Thermal Conductivitymentioning
confidence: 99%